article Clinical and Radiographic Comparative Study of Ferric Sulfate and Formocresol on Pulpotomy of Primary Molars: Clinical and Radiographic Comparative Study of Ferric Sulfate and Formocresol on Pulpotomy of Primary Molars (Journal of Hama University, 2024)
The aim of this study was to evaluate the efficacy of Ferric Sulphate (FS) in success of pulpotomy on primary teeth comparing with Formocresol(FC) by clinical and radiographic observation at (3,6,12) months. A total of 20 children aged (4-9) years having 40 first and second upper and lower molars were selected for traditional pulpotomy treatment, the teeth were divided randomly to be treated with either FC or FS, after the administration of anesthesia and isolation with the rubber dam, a routine pulpotomy was performed, and then application either FC or FS 15.5% (Astringedent®) techniques on radical pulp then a layer of ZOE was placed, then a base layer of zinc phosphate cement, teeth were finally restored by stainless steel crowns. Children were observed for (3, 6, 12) months. After follow-up periods ranging from 3-12 months the clinical success for FC and FS was (90%) in both groups. The radiographic success was 75% for FC and 80% for FS This study revealed at significance level 95% (P≤0.05) that the differences between the results of success of FS and FC were not statistically significant after (3,6,12) months.  FS can be used as an alternative agent to FC on pulpotomy of primary molars.
Keywords: : Formocresol, pulpotomy, Ferric sulfateic su